The African-American poet’s dilemma: Langston Hughes' and Countee Cullen's poetic response to a prejudiced world (Groundings Undergraduate, 2012)
The black poet’s identity is directly affected when living in a society of mixed messages caused by segregation laws, where socially he is deemed inferior, and consequently this is reflected in his poetry, as is the pressure of integrating with established white poetics forms. In an attempt to find a place in which to belong, he utilises his African heritage and a feeling of collectiveness within his community, but this is not always successful. More hope lies in his ability to assimilate into the American poetic structure, adding his own input along with the white literary canon.
Keywords: Langston Hughes; Countee Cullen; Poetry; Black; African-American; Prejudice; Identity; Segregation; Integration; Heritage